2020
DOI: 10.1093/clinchem/hvaa159
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive DNA Immune Repertoire Sequencing Using Unique Molecular Identifiers

Abstract: Background Immune repertoire sequencing of the T-cell receptor can identify clonotypes that have expanded as a result of antigen recognition or hematological malignancies. However, current sequencing protocols display limitations with nonuniform amplification and polymerase-induced errors during sequencing. Here, we developed a sequencing method that overcame these issues and applied it to γδ T cells, a cell type that plays a unique role in immunity, autoimmunity, homeostasis of intestine, sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The number of approaches and applications that use UMIs in sequencing is rapidly increasing. In cancer diagnostics, the use of UMIs is crucial since it allows to correct for both polymerase induced errors and amplification biases [10]. Many sample types and matrices are challenging to analyse due to limited amounts of DNA and enzymatic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The number of approaches and applications that use UMIs in sequencing is rapidly increasing. In cancer diagnostics, the use of UMIs is crucial since it allows to correct for both polymerase induced errors and amplification biases [10]. Many sample types and matrices are challenging to analyse due to limited amounts of DNA and enzymatic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular barcodes are random sequences, usually between four and fourteen nucleotides long, that enable tracking of all sequencing reads back to the original DNA molecule. Subsequently, unique molecular identifiers allow for correction of both DNA polymerase-induced errors [133] and uneven amplification [134] when used in combination with deep sequencing [135,136]. The requirement for deep sequencing limits ultrasensitive sequencing to targeted approaches due to costs.…”
Section: Circulating Tumor Dna Analysismentioning
confidence: 99%
“…In addition to inter-and intra-sample chimeras, another important factor that impedes Rep-seq applications is base errors introduced by PCR and HTS (28,34,(36)(37)(38). These base errors can be eliminated by taking consensus sequences (34,36).…”
Section: Dumparts Allows the Acquisition Of Accurate Antibody Repertoiresmentioning
confidence: 99%
“…It's reported that the substitution errors for amplicon sequencing have been greatly corrected by using quality score combined with Hamming graph and read overlapping (31). Moreover, amplification biases have been largely addressed by the introduction of unique molecular identifiers (UMIs), the random-tandem sequences with huge diversity, during reverse transcription (RT), thus subsequent PCR amplification of each cDNA molecule can be quantified and corrected by grouping antibodies based on UMIs or UMI pairs and subsequent consensus sequence building (28,29,(32)(33)(34)(35)(36)(37)(38). Besides, with the capability of tracking individual RNA molecules throughout PCR amplification and sequencing (33,35,39), UMIs also possess the potential for identifying and removing intra-sample chimeras.…”
Section: Introductionmentioning
confidence: 99%